Cross-sections for (p, x) reactions on natural chromium for the production of 52, 52m, 54Mn radioisotopes. (February 2015) - Wooten, A. Lake; Lewis, Benjamin C.; Lapi, Suzanne E.
Abstract: The production of positron-emitting isotopes of manganese is potentially important for developing contrast agents for dual-modality positron emission tomography and magnetic resonance (PET/MR) imaging, as well as for in vivo imaging of the biodistribution and toxicity of manganese. The decay properties of 52 Mn make it an excellent candidate for these applications, and it can easily be produced by bombardment of a chromium target with protons or deuterons from a low-energy biomedical cyclotron. Several parameters that are essential to this mode of production—target thickness, beam energy, beam current, and bombardment time—depend heavily on the availability of reliable, reproducible cross-section data. This work contributes to the routine production of 52g Mn for biomedical research by contributing experimental cross-sections for natural chromium ( nat Cr) targets for the nat Cr( p, x ) 52g Mn reaction, as well as for the production of the radiocontaminants 52m, 54 Mn. Graphical abstract: The production of positron-emitting isotopes of manganese is potentially important for developing contrast agents for dual-modality positron emission tomography and magnetic resonance (PET/MR) imaging, as well as for in vivo imaging of the biodistribution and toxicity of manganese. The decay properties of 52 Mn make it an excellent candidate for these applications, and it can easily be produced by bombardment of a chromium target with protons or deuterons from a low-energy biomedical cyclotron. Several parameters that are essential to this mode of production—target thickness, beam energy, beam current, and bombardment time—depend heavily on the availability of reliable, reproducible cross-section data. This work contributes to the routine production of 52g Mn for biomedical research by contributing experimental cross-sections for natural chromium ( nat Cr) targets for the nat Cr( p, x ) 52g Mn reaction, as well as for the production of the radiocontaminants 52m, 54 Mn. Highlights: Produced large batch of natural Cr foils for cyclotron bombardment. Bombarded stacked foil targets with protons <14 MeV to measure cross-sections. Report new cross-section results for the nat Cr( p, x ) 52 Mn, nat Cr( p, x ) 52m Mn, and nat Cr( p, x ) 54 Mn reactions.